2015
DOI: 10.1039/c5py00490j
|View full text |Cite
|
Sign up to set email alerts
|

Latex routes to graphene-based nanocomposites

Abstract: International audienceThis review article describes recent advances in the elaboration of graphene-based colloidal nanocomposites by the use of graphene or graphene oxide in heterophase polymerization systems. Two main routes are reviewed: latex blending and in situ polymerization. In the first strategy, a segregated network is formed by confining the graphenic fillers in the interstices between the latex particles during the drying process. The morphology of the network depends on the relative dimensions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 186 publications
(239 reference statements)
1
53
0
Order By: Relevance
“…Solution blending, which entails swelling of graphene/polymer with a suitable solvent, is associated with the issue of subsequent solvent removal . Physical mixing methods, which typically involve blending a polymer latex with graphene, may result in a so called cellular morphology (graphene walls and polymer cells)—however, it can be a significant challenge to retain such a morphology in the final nanocomposite . Moreover, blending techniques usually have issues with aggregation of GO sheets within the composite structure, leading to a heterogeneous filler distribution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution blending, which entails swelling of graphene/polymer with a suitable solvent, is associated with the issue of subsequent solvent removal . Physical mixing methods, which typically involve blending a polymer latex with graphene, may result in a so called cellular morphology (graphene walls and polymer cells)—however, it can be a significant challenge to retain such a morphology in the final nanocomposite . Moreover, blending techniques usually have issues with aggregation of GO sheets within the composite structure, leading to a heterogeneous filler distribution .…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that GO has amphiphilic properties and can act as surfactant in oil‐in‐water emulsions . The amphiphilic properties of GO enable it to remain at the interface between the aqueous and oil phase (solid/liquid or liquid/liquid) allowing stabilization of monomer droplets in an aqueous emulsion . Miniemulsion polymerization of GO‐based Pickering emulsions provides an attractive route to polymer nanoparticles armored with GO sheets .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of functional groups enables electrostatic stabilization of functionalized graphene dispersions in water and various organic media without addition of surfactants and other dispersing aids . Furthermore, aqueous graphene oxide and graphite oxide dispersions represent attractive intermediates for polymer nanocomposite formation via dispersion blending with polymer latex and by polymerization filling . However, the synthesis of high‐purity graphite oxide requires tedious purification and special safety and handling precautions taking into account its explosive nature …”
Section: Introductionmentioning
confidence: 99%
“…[88,89] Furthermore, aqueous graphene oxide and graphite oxide dispersions represent attractive intermediates for polymer nanocomposite formation via dispersion blending with polymer latex and by polymerization filling. [90] However, the synthesis of high-purity graphite oxide requires tedious purification and special safety and handling precautions taking into account its explosive nature. [91] Opposite to wet-chemistry processes which require extensive and expensive additional purification steps for solvent recovery and by-product removal, solvent-free mechanochemistry processes hold great promise regarding the environmentally friendly and sustainable syntheses of nanoparticles tailored for a variety of applications ranging from catalysis to electronics, advanced optics, and nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…These hybrid materials are typically pursued for their attractive properties; some examples include the enhancement of mechanical strength of a matrix relative to the neat polymer, response to an applied magnetic field, incorporation of nanomaterials with catalytic function as well as optical properties for diagnostic imaging . The range of materials used to prepare such nanocomposites is extensive, with published examples including natural and synthetic clays, (semi‐)metal oxide nanoparticles, graphene‐derived nanosheets, carbon nanotubes, layered double hydroxides, and quantum dots . Aside from the layer‐by‐layer deposition approach, the most common method of creating such composite materials is heterophase polymerization, which encompasses emulsion, miniemulsion and dispersion polymerization .…”
Section: Introductionmentioning
confidence: 99%